Harmonizable locally spatially isotropic random fields (1999)
In this paper, the local behavior of harmonizable spatially isotropic random fields is considered. Spectral representations are obtained for generalized and ordinary harmonizable spatially isotropic fields with spatially isotropic increments of order M. The representation of a field with spatially isotropic increments of order M is also presented.